Pelatihan Pembuatan dan Pengawasan Evaluasi Kinerja Administrasi Produksi Pada UKM Mamin Pakis Malang - Made Iska Aprilita Wardani; Muhammad Hasyim Ashari; Tasnim Nikmatullah Realita; Moh.Shabri S.; Kristin Juwita (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The effectiveness and  efficiency of the production administration at  MSMEs MAMIN Pakis process needs to be supported by competent human resources.  The reason for the dedication is because the production administration system is not yet perfect. The aim is to provide practical knowledge of strategy and application of performance evaluation in a continuous improvement manner. Targets of a continuous structured work evaluation system and employee motivation in improving performance. The training process carried out, namely manual data collection, structured recording of integrated production application program input for each department, provides important insight and becomes the basis for progress so that the discipline of manual data input and programs becomes an error controller.  Activities processed from analysis of errors in inputting service release materials increase success and insight into production administration performance in a sustaainable manner.